Symmetric vacua in heterotic M theory - Lukas, A; Ovrut, B (2000)
Symmetric vacua of heterotic M theory, characterized by vanishing cohomology classes of individual sources in the three-form Bianchi identity, are analyzed on smooth Calabi-Yau three-folds. We show that such vacua do not exist for elliptically fibered Calabi-Yau spaces. However, explicit examples are found for Calabi-Yau three-folds arising as intersections in both unweighted and weighted projective space. We show that such symmetric vacua can be combined with attractive phenomenological features such as three generations of quarks and leptons. Properties of the low energy effective actions associated with symmetric vacua are discussed. In particular, the gauge kinetic functions receive no perturbative threshold corrections, there are no corrections to the matter field Kähler metric and the associated five-dimensional effective theory admits flat space as its vacuum.